The presence of microplastics in the digestive tract of commercial fishes off Pantai Indah Kapuk coast, Jakarta, Indonesia - AYU RAMADHINI HASTUTI; DJAMAR TF LUMBANBATU; YUSLI WARDIATNO (Society for Indonesian Biodiversity, 2019)
Abstract. Hastuti AR, Lumbanbatu DTF, Wardiatno Y. 2019. The presence of microplastics in the digestive tract of commercial fishes off Pantai Indah Kapuk coast, Jakarta, Indonesia. Biodiversitas 20: 1233-1242. Microplastics in fishes have been reported in many studies due to their threat to marine fishes and human health. But only a few data exist on commercial fish for human consumption in Indonesia. This study revealed the presence of microplastics in the digestive tract of 9 commercial species collected from six sites along the Pantai Indah Kapuk coast. Ingested microplastics were identified using gut content analysis. Microplastic particles were counted and categorized by type, color, and size. 169 of 174 (97.13%) of examined fish had microplastics. A total of 2063 microplastic particles were collected with the average number of particles per individual of 12.21 ± 9.76. The highest number (20.0 ± 8.0 particles individual-1) was found in Sardinella fimbriata and the lowest one (4.9 ± 4.7 particles individual-1) was found in Oreochromis mossambicus. Majority of ingested particles were fibers (89.63%), followed by fragments (6.24%), films (4.13%) and no pellets were observed. In terms of color, the most abundant were transparent particles (79.20%), followed by blue (7.03%), red (3.54%), black (2.86%), green (2.71%), and others which were found in low number. The highest number of fibers by size was <20-100 µm (55.03%), films were 100 - 1000 µm (33.93%), and fragments were <100 µm (25.25%). Microplastics ingested per individual in each species were not correlated to total body length, total body weight, digestive tract length, digestive content weight, mouth height, and mouth length.